2017
DOI: 10.1177/0269216317710383
|View full text |Cite
|
Sign up to set email alerts
|

Which patients die in their preferred place? A secondary analysis of questionnaire data from bereaved relatives

Abstract: Positive associations were found between continuity of care between healthcare professionals and contact with the general practitioner and the chance of people dying in their preferred place. Moreover, special attention for people who have had a stroke and for people with dementia who want to die at home seems indicated as their diagnosis is negatively associated with dying in their preferred place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 18 publications
0
18
1
2
Order By: Relevance
“…Some previous studies have mentioned the importance of the place or environment at the end of life for people with dementia. Fukui et al, Fleming et al and Perrar et al reported that people with dementia are sensitive and have special needs regarding their environment (Badrakalimuthu and Barclay, 2014;Fleming et al, 2015;Fukui et al, 2011;Perrar et al, 2015). Despite its importance, people with dementia in our study and in previous studies probably experienced more difficulty fulfilling their hopes about their preferred place to die compared with people with other diseases (Badrakalimuthu and Barclay, 2014;Raijmakers et al, 2018;Sato et al, 2015).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Some previous studies have mentioned the importance of the place or environment at the end of life for people with dementia. Fukui et al, Fleming et al and Perrar et al reported that people with dementia are sensitive and have special needs regarding their environment (Badrakalimuthu and Barclay, 2014;Fleming et al, 2015;Fukui et al, 2011;Perrar et al, 2015). Despite its importance, people with dementia in our study and in previous studies probably experienced more difficulty fulfilling their hopes about their preferred place to die compared with people with other diseases (Badrakalimuthu and Barclay, 2014;Raijmakers et al, 2018;Sato et al, 2015).…”
Section: Discussioncontrasting
confidence: 53%
“…Fukui et al, Fleming et al and Perrar et al reported that people with dementia are sensitive and have special needs regarding their environment (Badrakalimuthu and Barclay, 2014;Fleming et al, 2015;Fukui et al, 2011;Perrar et al, 2015). Despite its importance, people with dementia in our study and in previous studies probably experienced more difficulty fulfilling their hopes about their preferred place to die compared with people with other diseases (Badrakalimuthu and Barclay, 2014;Raijmakers et al, 2018;Sato et al, 2015). Some guidelines recommend respecting the person's wishes regarding the place of death (Livingston et al, 2017;North West Coast Strategic Clinical Network, 2018;; however, this place may often be a nursing home to reduce caregiver burden (Livingston et al, 2017;.…”
Section: Discussionmentioning
confidence: 99%
“…Esta distribuição vai ao encontro das previsões da OMS, as quais estimam que 52% dos doentes a necessitar de cuidados paliativos seja do género masculino e 69% se encontre acima dos 60 anos. 17 Quanto à preferência de morte no domicílio obteve--se uma satisfação do desejo de apenas 32,3%, encontrando-se, sem dúvida, entre os valores mais baixos da literatura, [8][9][10]16,[18][19][20][21][22][23] com um valor k considerado apenas razoável.…”
Section: Discussionunclassified
“…Apesar de não serem conhecidos no nosso país, na literatura internacional foram já identificados, com alguma heterogeneidade, vários fatores que poderão facilitar a morte no domicílio entre os doentes que assim o desejam. Para além dos fatores relacionados com a doença e dos fatores relacionados com o indivíduo, [8][9][10] foram também identificados fatores ambientais, onde se destacam, como fatores facilitadores, as visitas domiciliárias de enfermagem, do médico de família e da equipa especializada em cuidados paliativos, [8][9][10][11] assim como o facto de o doente não se encontrar hospitalizado nos últimos três meses de vida, sendo cuidado no domicílio, e o facto de o doente discutir o tema do local de morte com os profissionais de saúde. 8,11 O objetivo do presente trabalho foi então identificar fatores associados à satisfação da preferência de morte no domicílio entre os doentes acompanhados em cuidados paliativos em Portugal.…”
unclassified
“…Krikorian et al (2010) reported that the experience of relatives at the time of death was more positive when they received support from the attending healthcare professionals. Other recent studies emphasized that the experience of relatives is more positive when the death occurs in the place preferred by the patient (Hoare et al, 2015;Raijmakers et al, 2018).…”
Section: Discussionmentioning
confidence: 99%